The Griffin's Riddle : The Imaginary Veterinary #5 - Selfors, Suzanne (New York ; Boston : Little, Brown and Company, 2015)
"Ten-year-olds Pearl and Ben, continuing their apprenticeships at Dr. Woo's Worm Hospital, discover that Dr. Woo and the sasquatch are both sick with Troll Tonsillitis, and they must travel to the Imaginary World to find the only cure: a griffin's feather"--
Keywords: Griffins -- Fiction; Imaginary creatures -- Fiction; Veterinarians -- Fiction; Apprentices -- Fiction